The family is a place of “learning” of dying - Sztobryn-Bochomulska, Justyna (Biografie rodzinne i uczenie się: Tom 8, 2021)
Death is one of those events that affects people’s lives – it overshadows, frightens, determines or destroys. It is not without significance what attitude a person takes towards it. Today’s perception of death created by pop culture is not conducive to build in people’s minds the image of death that would help in understanding its phenomenon. In this perspective, in the matter of death, one can not rely on the process of socialization itself, because that in mass culture is not only not excessive but even acts to the disadvantage of the individual. Therefore a family, the most primary place of education and socialization, should be the place that must provide the correct patterns of understanding and experiencing death. It is thanks to the family that a man at every stage of his development should have a chance to make a conscious effort to discover the meaning of death. The shaping of such a conscious attitude gives the chance not only to reduce existential anxiety or to cope better with loss but also affects the whole life of an individual.